Comparing the impact of spaced instruction and massed instruction in learning collocations among Iranian EFL learners - Ehsan Namaziandost; Choiril Anwar; Leila Neisi (EduLite: Journal of English Education, Literature and Culture, 2020)
This study compared the impact of spaced instruction and massed instruction on learning collocations among Iranian EFL learners. To do so, 60 Iranian pre-intermediate EFL learners were selected among 90 students based on the results of Oxford Quick Placement Test (OQPT). The selected participants were then non-randomly divided into two equal experimental groups; spaced group and massed group. Afterwards, the researcher measured the participants’ collocations knowledge by administering a collocation pre-test. Then, 100 English collocations were instructed to the both experimental groups in the treatment phase of the study. After the instruction, a collocation post-test was administered to both groups and finally the data were analyzed by using paired and independent samples t-tests. The obtained results indicated that there was a significant difference between the post-tests of spaced and massed groups. The findings indicated that the spaced group significantly outperformed the massed group (p < .05) on the post-test. The implications of this study can make the teachers aware that teaching through spaced intervals can provide better results than teaching through one massed session.